2009
DOI: 10.1029/2008gl036128
|View full text |Cite
|
Sign up to set email alerts
|

Nature of opaque components on Mercury: Insights into a Mercurian magma ocean

Abstract: [1] Analysis of Mariner 10 and MESSENGER data sets reveal the importance of opaque components on Mercury's surface. A global darkening agent, suggested to be ilmenite or other Fe-, Ti-bearing opaque mineral, has been invoked to explain the lower albedo of Mercury relative to the lunar highlands. Separately, a low-reflectance material (LRM) has been recognized as one of three dominant color terrains. We present laboratory reflectance spectra of ilmenite size separates and other candidate Fe-, Ti-bearing oxide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
2
51
0
Order By: Relevance
“…The low iron content confirms previous interpretations based on multispectral images (Blewett et al, 1997;McClintock et al, 2008) but the low titanium contents do not support a significant contribution by Ti-oxides in producing low-reflectance materials (Denevi et al, 2009;Riner et al, 2009Riner et al, , 2010Riner et al, , 2011Sprague et al, 2009;Lawrence et al, 2010). The SiO 2 content is high and ranges from 52 to 60 wt%.…”
Section: Calculations On An Oxide Basissupporting
confidence: 73%
“…The low iron content confirms previous interpretations based on multispectral images (Blewett et al, 1997;McClintock et al, 2008) but the low titanium contents do not support a significant contribution by Ti-oxides in producing low-reflectance materials (Denevi et al, 2009;Riner et al, 2009Riner et al, , 2010Riner et al, , 2011Sprague et al, 2009;Lawrence et al, 2010). The SiO 2 content is high and ranges from 52 to 60 wt%.…”
Section: Calculations On An Oxide Basissupporting
confidence: 73%
“…Denevi and Robinson (2008) determined the average reflectance of Mercury to be 15% lower than that of the average lunar nearside, $30% of which is covered by relatively low-reflectance mare basalts. Factors that may contribute to the low reflectance of Mercury include the presence of opaque phases (Denevi and Robinson, 2008;Denevi et al, 2009;Riner et al, 2009), a high abundance of microphase metallic iron particles produced by intense space weathering (Lucey and Riner, 2011;Riner and Lucey, 2012), and possibly spectral changes in minerals induced by heating to Mercury daytime temperatures (Helbert et al, 2013). Shkuratov et al (2012) found a stronger reflectancephase-ratio correlation for their higher-reflectance case than for their lower-reflectance case.…”
Section: Relationship Between Reflectance and Phase Ratiomentioning
confidence: 90%
“…Due in no small part to the lessons learned in developing and refining the LMO hypothesis, magma oceans have now been invoked on the basis of sample and remote sensing observations to explain the differentiation and lithological diversity of other terrestrial bodies such as Earth, Mars, Mercury and 4 Vesta (e.g. Ohtani, 1985;Tonks and Melosh, 1993;Li and Agee, 1996;Righter and Drake, 1997;Borg and Draper, 2003;Riner et al, 2009Riner et al, , 2010. However, large terrestrial planets at least partially obliterate the original products of their differentiation through post-magma ocean processes (i.e.…”
Section: Introductionmentioning
confidence: 99%